THE EFFECT OF SOLAR RADIATION ON THE SIGNAL STRENGTH OF A.B.U. SAMARU RADIO STATION (FUDMA JOURNAL OF SCIENCES, 2023)
Solar activities including solar radiations affects not only the electron content of the ionosphere but also the various frequencies used in telecommunications. The alternating voltages of the frequency modulation (FM) in Ahamdu Bello University radio station was obtained during the period of three months from July to September 2019. The variation of all prominent peaks of the electron density begins during sunrise and sunset, where most of the peaks shows weak signal strength during the daytime i.e. at 16,000N/m3 compared to night time and morning time at 0.00N/m3 and 0.00N/m3 respectively. The results showed that this station have all day signal strength, while night time show variability in signal strength. This observation may be attributed to the solar activity in the atmosphere. We calculated the critical frequency and hence find the Maximum Usable Frequency (MUF) and conclude that solar radiation factor give the minimum significant effect to radio signals.
Keywords: Solar; radiation; electromagnetic waves